Reflexiones sobre el Código Civil italiano y peruano - Benatti, Francesca (2020)
ADVOCATUS had the opportunity to interview Francesca Benatti, Italian lawyer and associate professor of Comparative Private Law at the University of Padua. In the following lines, the interviewee offers a brief analysis on the Peruvian Civil Code and the Italian Civil Code, addressing elements of Civil Law, including torts and Private Law, as well as comparative law.